2018
DOI: 10.1108/ijsi-02-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Seismic resistance prediction of corroded S400 (BSt420) reinforcing bars

Abstract: Purpose Structures in seismic areas, during their service lifetime, are subjected to numerous seismic loads that certainly affect their structural integrity. The degradation of these structures, to a great extent, depends on the scale of seismic events, the steel mechanical performance on reversal loads and its resistance to corrosion phenomena. The paper aims to discuss these issues. Design/methodology/approach Based on the experimental results of seismic steel behavior S400 (BSt III), which was widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In this framework, the influence of the shot blasting method on the fatigue response of steel reinforcing bars is studied. A correlative study in terms of load bearing capacity and energy absorption ability was conducted to assess the impact of loading history on the mechanical performance of steel reinforcement; thus, low cycle fatigue tests were carried out to simulate the consequences of seismic loading on steel rebars, as already indicated by several studies [19,37]. The results are demonstrated in Tables 7-9 for each tested group of specimens, along with the corresponding mass loss, where a gradual improvement of shot blasted specimens is clearly recorded in terms of percentage mass loss, service life, dissipated energy density, and the performance of maximum stress.…”
Section: Results Of Fatigue Testsmentioning
confidence: 99%
“…In this framework, the influence of the shot blasting method on the fatigue response of steel reinforcing bars is studied. A correlative study in terms of load bearing capacity and energy absorption ability was conducted to assess the impact of loading history on the mechanical performance of steel reinforcement; thus, low cycle fatigue tests were carried out to simulate the consequences of seismic loading on steel rebars, as already indicated by several studies [19,37]. The results are demonstrated in Tables 7-9 for each tested group of specimens, along with the corresponding mass loss, where a gradual improvement of shot blasted specimens is clearly recorded in terms of percentage mass loss, service life, dissipated energy density, and the performance of maximum stress.…”
Section: Results Of Fatigue Testsmentioning
confidence: 99%
“…The damage of materials due to fatigue is directly linked with their microstructure because the development and propagation of microcracks toward the inner part of the material is crucial for mechanical performance. In this framework, a complementary study by means of load-bearing capacity and ability for energy absorption was established to assess the impact of loading history on the mechanical performance of steel reinforcement; thus, low-cycle fatigue tests were conducted to simulate the consequences of seismic loadings on steel rebars, as already indicated by several studies [25,37]. The results are demonstrated in Tables 6 and 7 for each tested specimen, along with the corresponding mass loss.…”
Section: Results Of Fatigue Testsmentioning
confidence: 99%
“…More specifically, the experimental data do not outline any consequences additional to those that are already known, namely the percentage of mass loss and reduced cross-sectional area, the development of pits responsible for the development of stress concentration points, and the degradation of the mechanical behavior of reinforcing bars, as well as the cracking and spalling of concrete cover and reduced bond strength between steel and concrete. Thus, many researchers have paid attention to the coupled effect of dynamic loading along with the corrosive environment in RC structures [16,19,[33][34][35][36][37]. The overall current research indicates that the simultaneous actions of aggressive environmental effects and repeated loading increase the vulnerability of RC structures and diminish their bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers focused on the combined effect of cyclic loading during earthquakes and corrosion phenomena in structures (Dolley et al, 2000;Kashani et al, 2014;Veerman et al, 2015;Fernandez et al, 2015;Yi et al, 2011;Apostolopoulos et al, 2018). Dolley et al (2000) showed that the distribution of fatigue life is strongly correlated to the pits' geometry due to corrosion.…”
Section: Introductionmentioning
confidence: 99%